Multimodal Text Analysis of a Student’s Book for Grade VII of Junior High School - Ratih Sri Pramestri; Joko Priyana (Eduvest - Journal of Universal Studies, 2025)
This study investigates how multimodal texts in the English for Nusantara coursebook for Grade VII junior high school construct meaning through the integration of verbal and visual elements. The coursebook combines written language with various visual modes to facilitate meaning in classroom contexts, reflecting the increasing importance of multimodal resources in English language education. By employing Halliday’s Systemic Functional Linguistics (SFL) to analyze verbal texts and Kress and van Leeuwen’s Visual Grammar for visual texts, the research examines how these modes realize different meanings. A qualitative content analysis was conducted on selected chapters—“About Me,” “Culinary and Me,” and “Home Sweet Home”—which were rich in multimodal content. Verbal data were segmented and analyzed according to SFL metafunctions, while visual data focused on representation and interaction patterns. Findings reveal that meaning is constructed through the interplay of verbal and visual elements, with verbal texts primarily conveying ideational meaning and interpersonal roles, and visual texts utilizing narrative and conceptual structures. The study highlights a strong tendency toward equal status between verbal and visual modes, demonstrating the collaborative nature of meaning-making in multimodal educational texts. Overall, it underscores the complex strategies at work in the design of the coursebook.